KIE Hipertensi dan Jalan Kaki 30 Menit sebagai Intervensi Pencegahan dan Penanganan Hipertensi pada Masyarakat RW 02 Pakulonan Serpong Utara, Tangerang Selatan - Mustakim Mustakim; Thresya Febrianti (Jurnal Pengabdian Pada Masyarakat, 2020)
COMMUNICATION, INFORMATION AND EDUCATION OF HYPERTENSION AND 30 MINUTE WALKING AS AN INTERVENTION TO PREVENT AND MANAGE HYPERTENSION IN THE COMMUNITY OF RW 02 PAKULONAN SERPONG UTARA, TANGERANG SELATAN. In 2011 WHO recorded that prevalence of hypertension amounted to 1 billion people in the world. Two-thirds of them are in low-income countries, one of which is Indonesia. Preliminary studies found in Puskesmas Ciputat Timur that 7 out of 10 people had hypertension. We need to take intervention in preventing and treating through Communication, Information and Education (KIE) and 30 minutes walking every day. Result showed a good level of knowledge in hypertension that impact to their awareness in fighting hypertension. Then, this result was followed by strong commitment to prevent hypertension by 30 minutes walking every day. This physical activity are proven to reduce blood pressure if we have done it routinely. We hope that the community can maintain this positive activities with supported by the local policies.